Beneficial effects of miR-132/212 deficiency in the zQ175 mouse model of Huntington’s disease - Nateghi, Behnaz; Keraudren, Remi; Boulay, Gabriel; Bazin, Marc; Goupil, Claudia; Canet, Geoffrey; Loiselle, Andréanne; St-Amour, Isabelle; Planel, Emmanuel; Soulet, Denis; Hébert, Sébastien S. (Frontiers in Neuroscience, 2024)
Huntington’s disease (HD) is a rare genetic neurodegenerative disorder caused by an expansion of CAG repeats in the Huntingtin (HTT) gene. One hypothesis suggests that the mutant HTT gene contributes to HD neuropathology through transcriptional dysregulation involving microRNAs (miRNAs). In particular, the miR-132/212 cluster is strongly diminished in the HD brain. This study explores the effects of miR-132/212 deficiency specifically in adult HD zQ175 mice. The absence of miR-132/212 did not impact body weight, body temperature, or survival rates. Surprisingly, miR-132/212 loss seemed to alleviate, in part, the effects on endogenous Htt expression, HTT inclusions, and neuronal integrity in HD zQ175 mice. Additionally, miR-132/212 depletion led to age-dependent improvements in certain motor functions. Transcriptomic analysis revealed alterations in HD-related networks in WT- and HD zQ175-miR-132/212-deficient mice, including significant overlap in BDNF and Creb1 signaling pathways. Interestingly, however, a higher number of miR-132/212 gene targets was observed in HD zQ175 mice lacking the miR-132/212 cluster, especially in the striatum. These findings suggest a nuanced interplay between miR-132/212 expression and HD pathogenesis, providing potential insights into therapeutic interventions. Further investigation is needed to fully understand the underlying mechanisms and therapeutic potential of modulating miR-132/212 expression during HD progression.